A interação entre gerenciamento de projetos e gestão do conhecimento: estudos de casos múltiplos de tecnologia de informação em um banco brasileiro - Kuwamoto, Paula Emiko (2010)
This thesis gathers the key concepts in project management. It deals with the mechanisms and process related to the interproject knowledge management by an organization, in the pursuit of performance improvement in the overall project management. Thus, we propose a structure, composed by elements related with the explicit knowledge and also the tacit knowledge, as well as consideration of the organizational cultural factors involved. An explanatory qualitative research was performed - through multiple case studies in a Brazilian organization - to attest this structure. As a result, we find the evidence to confirm the structure, with the inclusion of new elements that influences the process. This study analyzed the process of interproject knowledge management in IT, which is fertile and has many opportunities of exploration, especially when considering the national situation.